Cross-Sectoral Synergy Measurement Framework for Multimodal NGOs in Public Health, Agriculture, and Education in Sub-Saharan Africa - Oluremi Nurudeen Olaleye; Ahmed Adebowale Adedeji; Tunde Biya Olakunle; Maryam Kofoworola Olaleye (The Indonesian Institute of Science and Technology Research, 2026)
Multimodal non-governmental organisations (NGOs) operating simultaneously across health, education, and agriculture represent an increasingly important vehicle for integrated development programming in Sub-Saharan Africa. However, these organisations face a persistent challenge: the absence of standardised metrics capable of capturing the complex cross-sectoral synergies that emerge when interventions in one domain interact with and amplify outcomes in another. This paper addresses this gap by proposing the Cross-Sectoral Synergy Measurement Framework (CSSMF), a three-tiered evaluation architecture comprising sector-specific indicators, cross-sectoral bridge indicators, and synergy indicators. Drawing on systems thinking, complexity theory, and integrated development theory, the CSSMF provides a structured yet flexible approach for practitioners and evaluators to measure not only direct programme outcomes but the emergent, non-linear interactions between health, education, and agriculture interventions. The framework is operationalised through a mixed-method evaluation design combining quasi-experimental quantitative approaches with participatory qualitative methods. Through an illustrative case application situated in the peri-urban communities of Lagos State, Nigeria, this paper demonstrates the practical applicability of the CSSMF and shows how integrated programming can produce measurable synergy gains of approximately 18 per cent above the summed effects of siloed delivery at 12 per cent lower cost per composite outcome unit. The paper concludes with recommendations for institutionalising cross-sectoral evaluation within the development sector and identifies priority areas for future research and empirical validation.